Cost analysis of the first line antiretroviral therapy in Russian Federation - A. V. Rudakova (Журнал инфектологии)
Costs of HIV-infection treatment in Russian Federation are a considerable burden on national resources.Study objective: calculation of one year costs for first line antiretroviral therapy (ART) according to Recommendations (clinical guidelines) of Russian Federal/National Research and Methodology Centre of AIDS Prevention and Treatment, with assessment of patient access within a fixed budget.Materials and methods: Cost calculation for acquisition of one year of ART is based on Emergency Drug List (EDL) registered prices by Ministry of Health including the VAT and 10% trade surplus. Comparisons are performed within treatment categories recommended by Russian clinical guidelines. ART selections within categories are assumed to be of similar efficacy and tolerability, according to Russian guidelines.Results and discussion: annual cost of first line ART per patient vary from 44 to 286 thousand RUR. The choice of ART is primarily based on clinical situation and co-morbidity. Among ART regimens in the same treatment category, assuming similar clinical efficacy and tolerability profiles, the less costly are preferable.Conclusions: comparison of alternative antiretroviral first line treatment regimens with comparable clinical efficacy and tolerability profiles demonstrates that cost minimization based on drug prices can grant access to treatment to maximum number of patients. Lopinavir/ritonavir is the less costly option in several guideline-recommended categories of first line regimens.